2017
DOI: 10.17711/sm.0185-3325.2017.022
|View full text |Cite
|
Sign up to set email alerts
|

An overview of repetitive transcranial magnetic stimulation (rTMS) in Alzheimer’s disease

Abstract: Background. Alzheimer's disease (AD) is the most frequent neurocognitive disorder. It affects 50% to 75% of the cases of dementia, and is characterized by a progressive cognitive decline that hinders behavior and functionality. Its etiology is still uncertain, and the efficiency of treatments is limited. Repetitive transcranial magnetic stimulation (rTMS) has been used as an alternative therapeutic strategy, but the clinical impact on Alzheimer's disease has hardly been studied. Objective. To describe the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Clinical trials using rTMS in AD have found positive effects on cognition, behavior and function (2)(3)(4). High frequency (HF) rTMS applied on the right or left DLPFC has shown improvement in language abilities, in cognitive function, functionality and behavior for up to 3 months (5).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials using rTMS in AD have found positive effects on cognition, behavior and function (2)(3)(4). High frequency (HF) rTMS applied on the right or left DLPFC has shown improvement in language abilities, in cognitive function, functionality and behavior for up to 3 months (5).…”
Section: Introductionmentioning
confidence: 99%